Analisis Penerapan Sistem Manajemen Keselamatan dan Kesehatan Kerja Di PT. PLN (Persero) Sektor Tambora Kabupaten Sumbawa Barat - Faathir Ilman, Abdillah (JPNM Jurnal Pustaka Nusantara Multidisiplin, 2024)
Occupational Safety and Health Management System (SMK3) is part of a management system that includes the company's organizational structure, planning, responsibility, implementation, achievement, assessment and development of occupational safety and health policies. PLN Tambora West Sumbawa is a business unit of PT PLN (Persero) which manages the electricity system in West Nusa Tenggara Province PT PLN (PERSERO) Tambora sector. In the Tambora sector, it was found that the implementation of SMK3 is still not effective, which can cause occupational accidents and occupational diseases such as the use of coal as a flammable material, slipping, falling from a height, disturbance, electric shock, and coal ash residue (FABA) which, if inhaled continuously, will cause respiratory problems. Continuous inhalation will cause respiratory distress. Therefore, an analysis was carried out on the implementation of the occupational safety and health system (SMK3) at PT PLN (PERSERO) by using data in the form of a questionnaire related to the implementation of the company's K3 management towards ISO 45001: 2018 and processing the data using the Gap Analysis method, then providing recommendations for improvement. The results showed that the implementation of ISO 45001: 2018 amounted to 88%. There is a gap of 12% because there are 4 clauses that have not been implemented optimally, namely clause 4.2 concerning understanding the needs and expectations of workers and other interested parties, clause 5.3 concerning roles, responsibilities and organizational management, clause 5.4 concerning worker consultation and participation and clause 7.2 concerning competence, so improvements are proposed for each clause.